Plants vs. zombies. 9, Greatest show unearthed - Tobin, Paul, 1965- (Dark Horse Books, 2018)
"Dr. Zomboss erroneously believes that all humans hold a secret desire to run away and join the circus, so he aims to use his new 'Big Z's Adequately Amazing Flytrap Circus' to lure Neighborville's citizens to their doom! Once plant-friendly neighborhood defenders Nate and Patrice infiltrate his show, Ringmaster Zomboss is in for a garden-ful of trouble!"--